(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the problem of spiritual and moral values of the Kyrgyz people in the conditions of modern realities. The main part of the Kyrgyz people based on traditional, spiritual and moral values. To this end, the author sets out to consider at the present stage the problem of spiritual and moral education of the younger generation. In this regard, the importance of studying oral folk art is noted. The article includes an analysis of spiritual and moral values in the epic “Manas”.